Program evaluation of STAR 360 : small scale proof of concept of the accuracy of the universal screener (STAR 360) in predicting students at-risk of failure in reading - Scott, Lisa T (East Carolina University, 2019)
The following was a program evaluation of the STAR 360 program in Moore County Schools at Vass-Lakeview Elementary from southern North Carolina and its impact on predicting students at-risk for failure in reading in First and Third Grade. STAR 360 is a universal screener that is utilized to assess and provide support to increase student reading and math achievement. The STAR 360 program provides valid, reliable screening, progress monitoring, and student growth data to make informed decisions about students. The results of this study showed that students who received sufficient instructional support as provided from the monitoring process of STAR 360 showed growth toward mastery of state learning standards in reading. The outcomes of the program determined the continued use of the STAR 360 program as a universal screener for the Moore County Schools District would be beneficial for teachers in utilizing the data to inform instruction.
Keywords: STAR 360; Academic achievement--North Carolina--Moore County; School children--North Carolina--Moore County; Reading--North Carolina--Moore County; Mathematics--Study and teaching--North Carolina--Moore County